Intersectional Lives Chinese Australian Women in White Australia - Kamp, Alanna (Taylor & Francis, 2022)
Intersectional Lives explores the varied experiences of Chinese Australian females across time and place during the White Australia Policy era (1901-1973). Chinese Australian women's personal reflections are examined alongside postcolonial feminist readings of official records to illustrate how their everyday lives were influenced by multiple and fluid identities and subject positions including migrant, mother, daughter, wife, student, worker, entrepreneur and cultural custodian. This book provides new ways to conceptualise Chinese females in the diaspora as gendered, classed, culturally varied and racialised individuals with multiple forms of oppression, agency and mobility. It offers a revision of patriarchal understandings of Chinese Australian history and broader understandings of overseas Chinese migrations and settlement experiences. It also demonstrates how historical geography, informed by postcolonial feminist approaches, can facilitate more nuanced understandings of past (and present) times and places that include women's diverse experiences at the domestic, local, national and international scale. This book will appeal to social and cultural geographers with additional audiences of interest in history and historical geography, ethnic and racial studies, gender studies, diaspora studies, migration studies, and gender and feminist studies.